Tingkat Pengetahuan Pasien Prolanis Terkait Edukasi Dagusibu Menggunakan Media Leaflet di Klinik Gracia Ungaran - Luh Putu Mahatrianti Eningsari; Soraya, Novalisa Nindhi; Suzan Septiana; Ristina Rahma Shinta Dewi; Agitya Resti Erwiyani; Istinatus Sunnah (Politeknik Piksi Ganesha Indonesia, 2025)
Self-medication is defined as the selection and use of drugs by individuals to treat self-recognized illnesses or symptoms. The risk of self-medication behavior will arise if it is done incorrectly. One of the causes of this inaccuracy could be DAGUSIBU's error. Dissemination of information about DAGUSIBU can be done using leaflets. The aim of this research is to determine the influence of leaflet media on the implementation of DAGUSIBU extension. The method used is a pre-experimental research method with a one group pre and post test design. The sampling technique used by researchers was purposive sampling. The resultsof this research showed that the average increase in participants' knowledge was 14.77%.